A Systematic Review: Outcomes in Adult Recurrent Respiratory Papillomatosis Treated with Intralesional Cidofovir or Bevacizumab. (March 2017) - Drejet, Sarah; Halum, Stacey; Brigger, Matthew; Skopelja, Elaine; Parker, Noah P.
Objectives: (1) To systematically identify studies evaluating the use of intralesional cidofovir or bevacizumab as an adjunct in adult recurrent respiratory papillomatosis, determine disease severity and functional outcomes, and assess study quality. (2) To compare outcomes between the 2 adjuncts. Data Sources: Ovid Medline, EMBASE, Scopus, andClinical-Trials.gov . Review Methods: Data sources were systematically searched. A priori inclusion and exclusion criteria were instituted. Quality was evaluated with the Newcastle-Ottawa Quality Assessment Scale. A priori criteria were instituted to select studies suitable for comparison. Results: A total of 254 identified studies led to 16 for full-text review, including 14 for cidofovir and 2 for bevacizumab. Disease severity outcomes were reported in all studies, including remission rate, Derkay scores, time interval between operations, and/or lesion volume reduction. Remission rate was the most commonly reported (14 studies). Functional outcomes were reported in 5 studies (36%), including quality-of-life questionnaires, acoustic/aerodynamic analysis, and perceptual voice analysis. Voice-related quality of life was the most commonly reported (2 studies). Of 16 studies, 12 (75%) were rated poor quality. Reports almost invariably showed improved disease severity and functional outcomes following treatment; however, variable outcome measures and inadequate follow-up disallowed direct comparison of adjuncts. Conclusion: Remission rate was the most commonly reported disease severity outcome, and voice-related quality of life was the most commonly reported functional outcome. Most studies were of poor quality. No studies met criteria for comparative analysis between adjuncts. Future research would be improved by reporting consistent and comparable disease severity and functional outcomes, treatment protocols, and follow-up.